A case of possible Kounis syndrome as a complication of scombroid syndrome - Stefano Rusconi; Antonio Villa (Journal of Health and Social Sciences, 2017)
Kounis syndrome is defined as the concurrence of acute coronary syndromes such as coronary spasm or acute myocardial infarction with conditions associated with activation of inflammatory mediators such histamine, arachidonic acid and various cytokines and chemokines. Recently, a variety of unusual etiologies have been reported, including scombroid syndrome. We present a case of a woman without previous history of cardiac diseases or cardiovascular risk factors, who presented to emergency department after the onset of flushing, asthenia, palpitations, burning sensation in the mouth having just eaten tuna. The electrocardiogram revealed a sinus tachycardia with diffuse ST segment depression. After therapy, in a short time symptoms recovered and a second electrocardiogram no longer showed any ST changes. These electrocardiographic changes observed in our case were probably due to transitory coronary vasospasm as described in type I variant of Kounis syndrome.